Two-dimensional single-layer highly-ordered mesoporous TiO2 nano net material as well as preparation method and application thereof

Through the soft micelle-guided assembly method of amphiphilic surfactant, a two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material with periodic arrangement of single-layer through-hole structures was prepared, which solved the limitations of existing materials in pore structure and electronic properties, achieved high rate performance and long cycle stability, and was suitable for negative electrode materials for lithium-ion or sodium ion batteries.

CN119581546AInactive Publication Date: 2025-03-07INNER MONGOLIA UNIVERSITY

Patent Information

Application Number
CN202510138580.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-08
Publication Date
2025-03-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing two-dimensional porous crystalline materials have limitations in electronic structure and material composition, and lack ideal holes with large pore sizes and controllable structures, which limits their performance in applications such as batteries.

Method used

By using a soft micelle-guided assembly method using an amphiphilic surfactant, a two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material with a periodic arrangement of single-layer through-pore structure was prepared. The preparation method of this material includes chelating the amphiphilic block copolymer, organic titanium compound and inorganic acid solution to form a titanium-containing composite single micelle precursor solution, and wrapping and aging through chloride salt crystals, and finally obtaining a two-dimensional single layer highly ordered mesoporous TiO2 nanomesh material through calcination.

Benefits of technology

This material exhibits high rate performance and long cycle stability. It is suitable for negative electrode active materials for lithium-ion batteries or sodium-ion batteries, and has good electrochemical properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581546A_ABST
    Figure CN119581546A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of batteries, and particularly relates to a two-dimensional single-layer highly-ordered mesoporous TiO2 nano net material and a preparation method and application thereof. The two-dimensional single-layer highly-ordered mesoporous TiO2 nano-net material provided by the invention has a two-dimensional lamellar structure with periodically arranged single-layer through holes, wherein the periodic arrangement is hexagonal close arrangement; and the thickness of the two-dimensional single-layer highly ordered mesoporous TiO2 nano net material is 10 to 20 nm. The two-dimensional single-layer highly-ordered mesoporous TiO2 nano-net material is ultrathin, short in pore channel and large in specific surface area, and provides abundant electrochemical active sites, and meanwhile, the mesoporous structure is beneficial to full contact and permeation of an electrolyte and the nano-net material, so that the electrochemical activity of the nano-net material is improved. When the material is used as a negative electrode active material of a lithium ion battery or a sodium ion battery, high rate performance and long cycle stability are shown.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of batteries, and in particular relates to a two-dimensional single-layer highly ordered mesoporous TiO2 nano-mesh material and a preparation method and application thereof. Background Art

[0002] The separation of graphene and its unique low-dimensional material properties have stimulated great interest in two-dimensional materials. Recently, two-dimensional porous crystalline materials have become a hot research topic in materials science and nanotechnology due to their size-selective molecular transport channels, tunable electronic band gaps, and enhanced edge active sites. These properties are further integrated into a material platform with an ultrathin monolayer structure, making two-dimensional porous crystalline materials ideal candidates for high-throughput nanosieves for separation, sensing, catalysis, energy storage, and conversion applications. However, the practical utility of these materials depends on whether they can induce the formation of periodic highly ordered nanopores to precisely tailor their surface structure and electronic properties. In this context, remarkable progress has been made in the synthesis of ultrathin porous graphene, zeolite, and metal / covalent organic framework (MOF / COF) monolayers with intrinsic periodic micropore arrays. Nevertheless, these materials still have limitations in electronic structure and material composition, and they usually lack ideal pores with large pore size and controllable structure. This defect greatly restricts the application of two-dimensional porous crystalline materials.

[0003] The soft micelle-guided assembly method using amphiphilic surfactants has shown great potential in the synthesis of two-dimensional periodically ordered mesoporous semiconductor materials. For example, surfactant-oligomer micelles can be self-assembled at the interface between two phases as building blocks. This process promotes the formation of a series of two-dimensional mesoporous crystalline nanosheets with complex structures and various components. However, the resulting two-dimensional mesoporous nanosheets usually contain randomly distributed holes and show multilayer micelle thickness, and the disordered long pores affect the efficiency of mass transfer and reaction in the pores. This limitation stems from the difficulty of precisely regulating the arrangement of monolayer surfactant-oligomer composite micelles at the interface. In traditional methods, surfactant-oligomer composite micelles (assembly units of mesoporous materials) are mostly thermodynamically unstable. This instability may lead to phase transitions or cause significant cross-linking between adjacent micelles, resulting in irregular pore structures and overly thick multilayer structures. Therefore, it remains a major challenge to synthesize high-quality two-dimensional mesoporous semiconductor materials with periodically arranged hole arrays in ultrathin lattices. Summary of the invention

[0004] In view of this, the purpose of the present invention is to provide a two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material and its preparation method and application. The material is ultra-thin, with periodic arrangement of mesopores, and exhibits high rate performance and long cycle stability when used as a negative electrode active material for lithium-ion batteries or sodium-ion batteries.

[0005] In order to achieve the above object, the present invention provides the following technical solutions: The present invention provides a two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material having a two-dimensional sheet structure of periodically arranged single-layer through holes, wherein the periodic arrangement is hexagonal close-packed; the thickness of the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material is 10-20 nm.

[0006] Preferably, the lateral size of the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material is 1-10 µm.

[0007] Preferably, the center distance between two adjacent through holes is 30-52 nm.

[0008] The present invention also provides a method for preparing the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material described in the above technical solution, comprising the following steps: The amphiphilic block copolymer, a good solvent for the amphiphilic block copolymer, an organic titanium compound, an inorganic acid solution and a hydrolysis inhibitor are mixed to carry out a chelating reaction to obtain a titanium-containing composite single micelle precursor solution; The titanium-containing composite single micelle precursor solution is used to encapsulate chloride salt crystals, and the obtained titanium-containing composite micelles encapsulate the chloride salt crystals and age them to obtain a single-layer ordered mesoporous composite sheet encapsulating the chloride salt crystals; The single-layer ordered mesoporous composite sheet wrapped with chloride salt crystals is calcined, and after removing the chloride salt crystals from the obtained calcined product, the two-dimensional single-layer highly ordered mesoporous TiO2 nano-mesh material is obtained.

[0009] Preferably, the amphiphilic block copolymer comprises an amphiphilic diblock copolymer or an amphiphilic triblock copolymer; the amphiphilic diblock copolymer comprises polyethylene oxide- block -polystyrene block copolymer; the amphiphilic triblock copolymer includes polyethylene oxide-polypropylene oxide-polyethylene oxide block copolymer; the organic titanium compound includes one or more of tetrabutyl titanate, titanium isopropoxide and titanium n-propoxide.

[0010] Preferably, the aging includes room temperature aging, low temperature aging after a first heating, and high temperature aging after a second heating in sequence; the temperature of the low temperature aging is 40-60°C; the temperature of the high temperature aging is 80-100°C; the time of the room temperature aging, low temperature aging and high temperature aging is independently 12-24h.

[0011] Preferably, the calcination includes low-temperature calcination and high-temperature calcination in protective gas, and a third calcination in air; the temperature of the low-temperature calcination is 300-400°C, and the insulation time is 1-3h; the temperature of the high-temperature calcination is 500-600°C, and the insulation time is 1-3h; the temperature of the third calcination is 500-600°C, and the insulation time is 1-3h.

[0012] The present invention also provides the use of the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material described in the above technical scheme or the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material prepared by the preparation method described in the above technical scheme as a negative electrode active material in lithium ion batteries and / or sodium ion batteries.

[0013] The present invention also provides a negative electrode, whose negative electrode active material is the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material described in the above technical solution or the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material prepared by the preparation method described in the above technical solution.

[0014] The present invention also provides a lithium ion battery or a sodium ion battery, comprising a positive electrode, a negative electrode, an electrolyte and a separator, wherein the negative electrode is the negative electrode described in the above technical solution.

[0015] The present invention provides a two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material, which has a two-dimensional sheet structure of periodically arranged single-layer through holes, wherein the periodic arrangement is hexagonal close-packed; the thickness of the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material is 10-20nm. The two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material has a porous network structure, resulting in a large specific surface area, thereby providing sufficient lithium and sodium ion embedding surface active sites, and the mesoporous structure can effectively promote the contact between the electrolyte and the negative electrode made of the material, which is conducive to the occurrence of redox reactions during the charge and discharge process. Compared with conventional mesoporous materials, the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material is ultra-thin, resulting in short pores, which is conducive to the rapid transmission of the electrolyte in the pores, and the two-dimensional ultra-thin structure can make the material more effectively release the stress caused by the embedding and extraction of lithium and sodium ions during the charge and discharge process, and maintain structural stability. In addition, the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material is non-toxic, titanium dioxide has good thermal and chemical stability, large specific surface area, many reaction sites, short pores, and the transmission of sodium ions in the pores and the diffusion in the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material are fast. Therefore, it exhibits good power density and long-term cycle stability in lithium and sodium ion batteries during charging and discharging, and is expected to have broad application prospects in the future energy industry.

[0016] The present invention also provides a method for preparing the above-mentioned two-dimensional monolayer highly ordered mesoporous TiO2 nanomesh material. The realization of self-limiting, long-range ordered monolayer assembly in the present invention mainly depends on the electrostatic interaction between monodispersed titanium oxide cluster-copolymer composite spherical single micelles. Initially, an inorganic acid solution is used as a poor solvent for the hydrophobic block to cause the microphase separation of the amphiphilic block copolymer in a good solvent, and the hydrophilic block of the amphiphilic block copolymer enters the poor solvent, and the hydrophobic block remains in the good solvent, which induces the amphiphilic block copolymer micellization into spherical micelles, with its hydrophobic block as the core and the hydrophilic block as the shell. Under the chelation of the hydrolysis inhibitor (organic carboxylic acid), part of the hydrolysis sites of the organic titanium compound are occupied by the ligands produced by the hydrolysis inhibitor, the hydrolysis reaction is inhibited, and the incomplete hydrolysis forms ligand-modified titanium oxide clusters. The titanium oxide oligomers formed by the aggregation of these titanium oxide clusters interact with the spherical micelle shell through hydrogen bonds and electrostatic attraction to form titanium oxide cluster-copolymer composite spherical micelles. On these titanium oxide clusters, the surface hydroxyl groups generated by the hydrolysis reaction are protonated under acidic conditions to form -OH2 +, so that the titanium oxide clusters carry a positive charge, and thus the spherical composite micelles show a strong positive charge. These spherical composite micelles with the same charge cannot aggregate due to mutual electrostatic repulsion, forming electrostatically stable monodisperse titanium oxide cluster-copolymer composite spherical single micelles in the solution, and obtaining a titanium-containing composite single micelle precursor solution; in the subsequent mixing process with chloride salt, the titanium-containing composite single micelle precursor solution spreads on the surface of the chloride salt crystal to form a liquid film. The upper surface of the thinned solution layer presses the dispersed titanium oxide cluster-copolymer composite single micelles to the liquid-solid interface. The electrostatic repulsion between micelles prevents the composite single micelles from being in close contact through van der Waals attraction, so the composite single micelles are dispersed on the chloride salt crystal in a mutually spaced manner. Once a monolayer structure is formed, the electrostatic repulsion also hinders the further stacking of excess single micelles. These excess single micelles can be removed by solid-liquid separation along with the excess solution, resulting in the termination of the deposition of the composite single micelles in a self-limiting manner, thereby forming a uniform micelle monolayer on the surface of the chloride salt crystal. The arrangement and further assembly of the single-layer composite micelles occur during the aging step, during the solvent evaporation process on the surface of the chloride crystals. When the thickness of the liquid film on the surface of the chloride crystals is thin enough, the composite micelles begin to protrude from the surface of the liquid film. The capillary force caused by the deformation of the liquid surface pulls these composite micelles closer to each other, and finally connects them together in a hexagonal close-packed manner to form a single-layer two-dimensional sheet structure. Then, during the calcination process, the block copolymer is removed, and at the same time, the titanium oxide oligomer skeleton crystallizes to form titanium dioxide and shrinks in volume. The cavities occupied by the hydrophobic blocks in the micelle core in the sheet are opened from the upper and lower surfaces of the sheet to form through holes, and a two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material is obtained. Finally, the chloride crystals in the resulting calcined product are removed to obtain a self-supporting two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material. This method can achieve self-limited single-layer assembly on the surface of the chloride crystal, and finally obtain an ultra-thin two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a SEM image of a two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material prepared in Example 1; Figure 2 TEM image of the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material prepared in Example 1; Figure 3 HR-TEM image and SAED image of the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material prepared in Example 1; Figure 4 HAADF-STEM and EDS elemental analysis diagram of the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material prepared in Example 1; Figure 5 The AFM test image and single layer thickness information image of the two-dimensional single layer highly ordered mesoporous TiO2 nanomesh material prepared in Example 1; Figure 6 The XRD pattern of the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material prepared in Example 1; Figure 7 The nitrogen adsorption-desorption isotherm and pore size distribution diagram of the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material prepared in Example 1; Figure 8 TEM images of two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh materials with different through-hole center distances; Fig. 9 This is a cycle test diagram of a sodium ion battery when the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material prepared in Example 1 is used as the negative electrode; Fig.10 This is a rate test diagram of a sodium ion battery when the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material prepared in Example 1 is used as the negative electrode; Fig.11 This is a SEM image of a two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material prepared in Example 5; Fig.12 This is a SEM image of a two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material prepared in Example 6; Fig.13 This is a SEM image of a two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material prepared in Example 7; Fig.14 TEM image of a two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material prepared in Example 8; Fig.15 TEM image of the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material prepared in Example 9; Fig.16 TEM image of a two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material prepared in Example 10; Fig.17 TEM image of the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material prepared in Example 11; Fig.18 TEM image of the mesoporous TiO2 bulk material prepared in Comparative Example 1; Fig.19 This is a SEM image of the mesoporous TiO2 thin film material prepared in Comparative Example 2; Fig. 20 This is the SEM image of the mesoporous TiO2 thin film material prepared in Comparative Example 3. DETAILED DESCRIPTION

[0018] The present invention provides a two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material having a two-dimensional sheet structure of periodically arranged single-layer through holes, wherein the periodic arrangement is hexagonal close-packed; the thickness of the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material is 10-20 nm.

[0019] Unless otherwise specified, the present invention has no special requirements on the sources of the raw materials used, and commercially available products known to those skilled in the art may be used.

[0020] As an implementation mode, the thickness of the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material is 10~20nm, and in a specific embodiment, it is 15~17nm; the diameter of the through holes in the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material is 20~30nm, and in a specific embodiment, it is 25nm, and the shortest distance between adjacent through hole edges is 5~30nm, and in a specific embodiment, it is 5.2nm, 13.0nm, 18.2nm or 26.4nm; the through holes are quasi-circular.

[0021] As an embodiment, the component of the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material is anatase phase TiO2; the lateral size of the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material is 1-10 μm, and in a specific embodiment, it is 1-6 μm, and the specific surface area is 85-118 m 2 ·g -1 , in the specific embodiment, 97~110m 2 ·g -1 .

[0022] As an implementation mode, the center distance between two adjacent through holes is 30-52 nm, and in specific embodiments is 30.2 nm, 38.0 nm, 43.2 nm or 51.4 nm.

[0023] The two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material provided by the present invention is ultra-thin, resulting in short pores, which is beneficial to the rapid transmission of electrolyte in the pores. The porous network structure gives it a large specific surface area, providing abundant electrochemical active sites. At the same time, the mesoporous structure is beneficial to the full contact and penetration of the electrolyte with it, and when it is used as a negative electrode material for sodium ion batteries, it exhibits high rate performance and long cycle stability.

[0024] The present invention also provides a method for preparing the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material described in the above technical solution, comprising the following steps: The amphiphilic block copolymer, a good solvent for the amphiphilic block copolymer, an organic titanium compound, an inorganic acid solution and a hydrolysis inhibitor are mixed to carry out a chelating reaction to obtain a titanium-containing composite single micelle precursor solution; The titanium-containing composite single micelle precursor solution is used to encapsulate chloride salt crystals, and the obtained titanium-containing composite micelles encapsulate the chloride salt crystals and age them to obtain a single-layer ordered mesoporous composite sheet encapsulating the chloride salt crystals; The single-layer ordered mesoporous composite sheet wrapped with chloride salt crystals is calcined, and after removing the chloride salt crystals from the obtained calcined product, the two-dimensional single-layer highly ordered mesoporous TiO2 nano-mesh material is obtained.

[0025] The invention mixes an amphiphilic block copolymer, a good solvent of the amphiphilic block copolymer, an organic titanium compound, an inorganic acid solution and a hydrolysis inhibitor to carry out a chelating reaction, thereby obtaining a titanium-containing composite single micelle precursor solution.

[0026] As an embodiment, the amphiphilic block copolymer includes an amphiphilic diblock copolymer or an amphiphilic triblock copolymer; the amphiphilic diblock copolymer includes polyethylene oxide- block -polystyrene block copolymer (PEO- b -PS); the amphiphilic triblock copolymer includes polyethylene oxide-polypropylene oxide-polyethylene oxide block copolymer (PEO-PPO-PEO); the weight average molecular weight of the amphiphilic block copolymer is 20,000-50,000, and in a specific embodiment is 30,000-40,000.

[0027] As an embodiment, the good solvent of the amphiphilic block copolymer includes tetrahydrofuran and / or ethanol, and in a specific embodiment, it is tetrahydrofuran, or tetrahydrofuran and ethanol; the volume ratio of the tetrahydrofuran and ethanol is 7~9:3~1, and in a specific embodiment, it is 8:2; the ratio of the mass of the amphiphilic block copolymer to the volume of the good solvent of the amphiphilic block copolymer is (0.01~0.1) g:(2~20) mL, and in a specific embodiment, it is (0.02~0.05) g:(3~10) mL.

[0028] Using inorganic acid solution as a poor solvent for the hydrophobic block causes the amphiphilic block copolymer in the good solvent to undergo microphase separation. The hydrophilic block of the amphiphilic block copolymer enters the poor solvent, while the hydrophobic block remains in the good solvent, which induces the amphiphilic block copolymer to micellize into spherical micelles with its hydrophobic block as the core and the hydrophilic block as the shell.

[0029] As an embodiment, the organic titanium compound includes one or more of tetrabutyl titanate (TBOT), titanium isopropoxide and titanium n-propoxide, and in a specific embodiment, it is tetrabutyl titanate; the mass ratio of the amphiphilic block copolymer and the organic titanium compound is 0.01~0.1:0.1~0.8, and in a specific embodiment, it is 0.02~0.05:0.2~0.5. The present invention controls the number of cluster oligomers assembled with the amphiphilic block copolymer to form micelles by adjusting the amount of organic titanium compound added, thereby adjusting the pore wall thickness of the two-dimensional mesoporous array formed by the two-dimensional assembly of the composite micelles. Within the ratio range of the above-mentioned amphiphilic block copolymer and the organic titanium compound, the amount of organic titanium compound added is increased, so that the titanium oxide oligomers assembled with the amphiphilic block copolymer to form micelles increase, and the pore wall of the two-dimensional mesoporous array formed by the two-dimensional assembly of the composite micelles is thickened. Therefore, the center distance between two adjacent mesopores can be adjusted by changing the ratio of the organic titanium compound to the amphiphilic block copolymer.

[0030] As an embodiment, the inorganic acid solution includes a hydrochloric acid solution; the mass concentration of the hydrochloric acid solution is 30~37%, and in a specific embodiment it is 37%; the ratio of the mass of the organic titanium compound to the volume of the inorganic acid solution is (0.1~0.8) g:(0.5~2.5) mL, and in a specific embodiment it is (0.2~0.5) g:(1~2) mL.

[0031] H generated by inorganic acid solution + Combined with the block copolymer to protonate it and bind to the Cl - The electrostatic interaction is generated, which promotes the binding of the hydrolyzed organic titanium compound to the hydrophilic block of the amphiphilic block copolymer through hydrogen bonding or electrostatic interaction; + It also combines with -OH produced by hydrolysis of organic titanium compounds to produce -OH2 + , making the partially hydrolyzed titanium oligomer positively charged; Cl - The coordination effect can inhibit the hydrolysis rate of organic titanium compounds to a certain extent.

[0032] As an embodiment, the hydrolysis inhibitor includes acetic acid and / or acetylacetone, and in a specific embodiment, it is acetic acid; the mass concentration of the hydrolysis inhibitor is 95-98%, and in a specific embodiment, it is 98%; the mass of the organic titanium compound and the volume ratio of the hydrolysis inhibitor are (0.1-0.8) g: (0.5-2.5) mL, and in a specific embodiment, it is (0.2-0.5) g: (0.5-2) mL. The hydrolysis inhibitor can inhibit the rate of hydrolysis of the organic titanium compound. After the hydrolysis inhibitor is coordinated with the organic titanium compound, it can separate the titanium, occupy the hydrolysis site, and hinder the surrounding hydrolysis sites from continuing to hydrolyze, so that the partially hydrolyzed organic titanium compound can fully combine with the hydrophilic block of the amphiphilic block copolymer.

[0033] Hydrochloric acid mainly plays a bridging role in promoting the binding of the hydrolyzed organic titanium compounds to the hydrophilic blocks of the amphiphilic block copolymers through hydrogen bonds or electrostatic interactions. The acetic acid molecules can coordinate with the organic titanium compounds, and because of their steric hindrance effect, they can effectively inhibit the hydrolysis of the organic titanium compounds and promote the formation of stable pre-hydrolyzed titanium oxide clusters.

[0034] As an embodiment, the temperature of the chelating reaction is room temperature; the time of the chelating reaction is 2 to 6 hours, and in a specific embodiment, it is 3 to 5 hours; the chelating reaction is carried out under stirring; the stirring rate is 200 to 1000 rpm, and in a specific embodiment, it is 300 to 500 rpm.

[0035] The organic titanium compound is coordinated with an inorganic acid solution and a hydrolysis inhibitor to form a chelate. The organic titanium compound is incompletely hydrolyzed to form titanium oxide clusters. The titanium oxide oligomers formed by the aggregation of these titanium oxide clusters are combined with the hydrophilic block of the amphiphilic block copolymer through hydrogen bonds or electrostatic interactions, and assembled with the amphiphilic block copolymer to form the outer shell of a spherical composite single micelle, with the hydrophobic block of the amphiphilic block copolymer as the inner core.

[0036] After obtaining the titanium-containing composite single micelle precursor solution, the present invention uses the titanium-containing composite single micelle precursor solution to wrap chloride salt crystals, and the obtained titanium-containing composite micelles wrap the chloride salt crystals for aging to obtain a single-layer ordered mesoporous composite sheet wrapped with the chloride salt crystals.

[0037] As an embodiment, the chloride salt crystals include potassium chloride and / or sodium chloride; the ratio of the volume of the titanium-containing composite single micelle precursor solution to the mass of the chloride salt crystals is (0.5~5) mL:(5~50) g, and in a specific embodiment it is (1~4) mL:(20~40) g.

[0038] As an embodiment, the titanium-containing composite single micelle precursor solution is used to encapsulate chloride salt crystals by mixing the titanium-containing composite single micelle precursor solution and chloride salt crystals, shaking them well and then centrifuging them; the centrifugal speed is 2000~7000rpm, and in a specific embodiment, it is 3000~6000rpm; the centrifugal time is 3~15min, and in a specific embodiment, it is 5~10min.

[0039] During the mixing process, the composite single micelles in the titanium-containing composite single micelle precursor solution settle on the surface of the chloride salt crystals. After a sufficient layer of composite single micelles is deposited, the subsequent composite single micelles will not be able to continue to deposit due to the electrostatic repulsion of the first layer of deposited micelles. This self-limiting process causes a single layer of composite single micelles to be deposited on the surface of the chloride salt crystals.

[0040] As an embodiment, the aging includes room temperature aging, low temperature aging after a first heating, and high temperature aging after a second heating in sequence; the aging is carried out in an environment with a relative humidity of 30-60%, and 40-50% in a specific embodiment; the temperature of the room temperature aging is 25-30°C, and 25°C in a specific embodiment; the temperature of the low temperature aging is 40-60°C, and 40-50°C in a specific embodiment; the temperature of the high temperature aging is 80-100°C, and 80-90°C in a specific embodiment; the time of the room temperature aging, low temperature aging and high temperature aging is independently 12-24h, and 12-20h in a specific embodiment; the first heating rate is 1-5°C / min, and 2-3°C / min in a specific embodiment; the second heating rate is 1-5°C / min, and 2-3°C / min in a specific embodiment.

[0041] The humidity during the aging process should be controlled at a low level. Excessive humidity will cause the moisture in the air to aggravate the uncontrollable hydrolysis and curing of the titanium-containing precursor, affecting the orderly assembly of the titanium-containing composite single micelles. Under appropriate humidity conditions, low temperature conditions can control the slow curing of the titanium-containing precursor to coordinate the assembly process of the micelles; high temperature conditions can achieve a higher degree of curing of the titanium precursor skeleton that has been orderly assembled at low temperatures. The aging time can control the degree of hydrolysis and curing of the titanium precursor skeleton.

[0042] In the titanium-containing composite single micelle precursor solution, titanium oxide oligomers and amphiphilic block copolymers assemble to form titanium oxide cluster-copolymer composite spherical single micelles. The outer shell of the titanium oxide oligomer of the composite spherical single micelle carries a positive charge. The composite single micelles repel each other due to the same charge. Therefore, stable and uniform composite spherical single micelles can be obtained in the precursor solution as the building unit of the two-dimensional nanonet, which can be uniformly deposited on the surface of the chloride crystal. After a layer of composite single micelles is deposited on the surface of the chloride crystal, due to the mutual repulsion, subsequent composite micelles are difficult to continue to deposit. With the assistance of centrifugal force, the excess composite micelles are removed, leaving only a uniform single layer of composite micelles on the surface of the chloride crystal. Then, during the aging process, the solvent evaporates, and the capillary force drives the single layer of single micelles to assemble close to each other. At the same time, the mutual repulsion between micelles promotes the adjustment of the position of the single micelles to the optimal position with the lowest energy during the assembly process, forming a highly ordered mesoscopic structure. The invention uses readily available chloride crystals as templates and combines simple centrifugation technology to prepare a two-dimensional single-layer highly ordered mesoporous TiO2 nano-mesh material. The method has simple process, low cost and simple operation.

[0043] Discrete monolayer titanium oxide cluster-copolymer composite spherical single micelles assemble into a monolayer ordered mesoscopic structure on the surface of chloride salt crystals. During the room temperature aging process, the titanium-containing composite single micelle precursor solution covering the surface of chloride salt crystals slowly evaporates. As the solution becomes less and less, the discrete monolayer spherical composite single micelles are gradually pulled closer by capillary forces and finally connected into a piece in a hexagonal ordered assembly, forming a two-dimensional sheet with a monolayer hexagonal spherical pore structure; the low-temperature aging process causes the titanium-containing precursor skeleton of the two-dimensional sheet to slowly crosslink and solidify to prevent the curing process from causing the destruction of the highly ordered mesoscopic structure; finally, the high-temperature aging process causes the titanium-containing precursor skeleton to further crosslink and solidify.

[0044] After obtaining the single-layer ordered mesoporous composite sheet wrapped with chloride crystals, the present invention calcines the single-layer ordered mesoporous composite sheet wrapped with chloride crystals, and after removing the chloride crystals from the obtained calcined product, the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material is obtained.

[0045] As an embodiment, the equipment used for the calcination is a tubular furnace; the calcination includes low-temperature calcination and high-temperature calcination in a protective gas in sequence, and a third calcination in the air; the protective gas is nitrogen.

[0046] As an implementation mode, the temperature of the low-temperature calcination is 300~400°C, and in a specific embodiment, it is 300~350°C. The insulation time is 1~3h, and in a specific embodiment, it is 2~3h; the heating rate from room temperature to the temperature of the low-temperature calcination is 1~5°C / min, and in a specific embodiment, it is 3~5°C / min.

[0047] As an implementation mode, the temperature of the high-temperature calcination is 500~600°C, and in a specific embodiment, it is 500~550°C. The insulation time is 1~3h, and in a specific embodiment, it is 1~2h; the heating rate from the temperature of the low-temperature calcination to the temperature of the high-temperature calcination is 1~5°C / min, and in a specific embodiment, it is 3~5°C / min.

[0048] As an embodiment, before the third calcination, it also includes: cooling the product of the high-temperature calcination to room temperature; the temperature of the third calcination is 500~600℃, 500~550℃ in the specific embodiment, and the insulation time is 1~3h, 2~3h in the specific embodiment; the heating rate from room temperature to the temperature of the third calcination is 1~5℃ / min, 3~5℃ / min in the specific embodiment.

[0049] During the low-temperature calcination process in the protective gas, the titanium-containing precursor begins to crystallize to generate titanium dioxide. At the same time, the amphiphilic block copolymer is carbonized and hardened in the protective gas, which supports the mesostructure. Then the high-temperature calcination process further improves the crystallinity of titanium dioxide, and further calcination in the air is carried out to remove the amphiphilic block copolymer.

[0050] As an embodiment, the method for removing chloride salt crystals is: washing the calcined product with water; the washing is mixing the calcined product with water and stirring to dissolve the chloride salt crystals and separate the solid and liquid; the water is deionized water; the solid-liquid separation is filtering; the washing times are 2 to 3 times, and 3 times in a specific embodiment. The present invention thoroughly dissolves the chloride salt crystals in the calcined product by washing with excess water, thereby obtaining a self-supporting two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material.

[0051] As an embodiment, after removing the chloride salt crystals, the method further includes: drying the calcined product after removing the chloride salt crystals; the drying temperature is 40-80° C., and in a specific embodiment, it is 50-70° C.; the drying time is 12-24 hours, and in a specific embodiment, it is 12-20 hours.

[0052] The present invention synthesizes a two-dimensional ultrathin mesoporous monolayer TiO2 nanonet with a periodically arranged mesoporous array for the first time through a new self-limiting modular monolayer micelle assembly method. The main feature of this method is to use a hydrolysis inhibitor to regulate the hydrolysis of organic titanium compounds. The stabilizer hydrolysis inhibitor can quickly coordinate with the organic titanium compounds to form a chelate, effectively limiting its hydrolysis site, inhibiting its hydrolysis and further cross-linking reaction. These pre-hydrolyzed titanium oxide oligomers are assembled with amphiphilic block copolymers to form a unique charged titanium oxide oligomer-amphiphilic block copolymer composite spherical single micelle with electrostatic stability, and then the micelle monolayer is assembled by centrifugation on a chloride crystal substrate. This unique method induces the growth of a two-dimensional ultrathin mesoporous TiO2 nanonet with a highly ordered mesoporous array. The self-supporting mesoporous monolayer TiO2 nanonet obtained after removing the amphiphilic block copolymer template and the chloride crystal substrate shows a highly uniform ultrathin nano-perforated two-dimensional morphology with a large lateral size of several microns and a single layer of mesopores. The mesopores in the plane are arranged hexagonally and have long-range order, forming a highly periodic mesoporous array. By adjusting the ratio of organic titanium compounds and amphiphilic block copolymers, the number of titanium oxide oligomers assembled with amphiphilic block copolymers to form composite spherical single micelles is controlled, thereby adjusting the pore wall thickness of the two-dimensional mesoporous array formed by the two-dimensional assembly of composite spherical single micelles and the center distance of adjacent mesopores, and obtaining a periodically controllable ordered mesoporous array. The obtained two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material has a large specific surface area and a highly crystalline ultra-thin perforated framework, and exhibits good electrochemical performance as a negative electrode active material for lithium-ion batteries or sodium-ion batteries.

[0053] The present invention also provides the use of the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material described in the above technical solution or the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material prepared by the preparation method described in the above technical solution in lithium ion batteries and / or sodium ion batteries.

[0054] The present invention also provides a negative electrode, whose negative electrode active material is the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material described in the above technical solution or the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material prepared by the preparation method described in the above technical solution.

[0055] As an embodiment, the preparation method of the negative electrode comprises the following steps: mixing a two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material, a conductive agent, a binder and a solvent, coating the obtained mixed slurry on the surface of a substrate, and drying to obtain the negative electrode; the conductive agent is carbon black; the binder is sodium carboxymethyl cellulose; the solvent is isopropanol; the mass ratio of the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material, the conductive agent, the binder and the solvent is 8:1:1:10; the substrate is a copper sheet; the drying temperature is 70-80°C, and is 80°C in a specific embodiment; the drying equipment is a vacuum oven; the vacuum degree of the vacuum oven is 90-130Pa, and is 100-120Pa in a specific embodiment; the present invention has no special limitation on the drying time, until it is completely dried; the loading amount of the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material in the negative electrode is 2.0mg·cm -2 .

[0056] The present invention also provides a lithium ion battery or a sodium ion battery, comprising a positive electrode, a negative electrode, an electrolyte and a separator, wherein the negative electrode is the negative electrode described in the above technical solution.

[0057] As an embodiment, the positive electrode is metallic sodium or metallic lithium; the method for preparing the electrolyte of the sodium ion battery comprises the following steps: dissolving 1.0 mol / L NaClO4 in ethylene carbonate (EC) and propylene carbonate (PC) in a volume ratio of 1:1; the separator is glass microfiber.

[0058] As an embodiment, the preparation method of the lithium ion battery or sodium ion battery is: assembling the positive electrode, the negative electrode, the electrolyte and the diaphragm in a glove box filled with argon gas, and the obtained button battery is the lithium ion battery or the sodium ion battery.

[0059] The technical solutions of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention, but they should not be construed as limiting the protection scope of the present invention.

[0060] Example 1 0.05g PEO- b -PS (weight average molecular weight of 40000) was added with 10 mL of tetrahydrofuran solution, followed by 1.0 mL of 37 wt% hydrochloric acid, 1.0 mL of 98 wt% acetic acid and 0.40 g of TBOT, and the mixture was stirred at 300 rpm for 5 h at room temperature for chelation reaction to obtain a titanium-containing composite single micelle precursor solution; 1 mL of the titanium-containing composite single micelle precursor solution was poured into a centrifuge tube containing 20 g of sodium chloride crystals, shaken and centrifuged at 5000 rpm for 10 min, and the obtained titanium-containing composite micelles encapsulating the sodium chloride crystals were transferred to a culture dish and aged at 50% relative humidity and 25°C for 12 h, then transferred to an oven, heated to 40°C at 3°C / min at 50% relative humidity for 12 h, and then heated to 80°C at 3°C / min for 12 h to obtain a single-layer ordered mesoporous composite sheet encapsulating the sodium chloride crystals; The single-layer ordered mesoporous composite sheet wrapped with sodium chloride crystals is calcined in a tubular furnace, and the calcination steps are as follows: heating from room temperature to 300°C at 5°C / min in nitrogen for 3 hours, then heating to 500°C at 5°C / min and continuing to calcine for 1 hour, after cooling to room temperature, transferring to a muffle furnace, heating from room temperature to 500°C at 5°C / min in air and calcining for 3 hours, finally mixing the calcined product with deionized water and stirring to dissolve the chloride crystals, filtering the washing liquid, repeating the water washing twice, and drying the obtained solid at 60°C for 12 hours to obtain a two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material.

[0061] Example 2 The difference from Example 1 is that the amount of tetrabutyl titanate added is 0.2 g.

[0062] Example 3 The difference from Example 1 is that the amount of tetrabutyl titanate added is 0.3 g.

[0063] Example 4 The difference from Example 1 is that the amount of tetrabutyl titanate added is 0.5 g.

[0064] Example 5 The difference from Example 1 is that the organic solvent is 9 mL of tetrahydrofuran and 1 mL of ethanol.

[0065] Example 6 The difference from Example 1 is that the organic solvent is 8 mL of tetrahydrofuran and 2 mL of ethanol.

[0066] Example 7 The difference from Example 1 is that the organic solvent is 7 mL of tetrahydrofuran and 3 mL of ethanol.

[0067] Example 8 The difference from Example 1 is that the amount of acetic acid added is 0.5 mL.

[0068] Example 9 The difference from Example 1 is that the amount of acetic acid added is 2 mL.

[0069] Example 10 The difference from Example 1 is that the centrifugal speed is 3000 rpm.

[0070] Embodiment 11 The difference from Example 1 is that the centrifugal speed is 6000 rpm.

[0071] Comparative Example 1 The difference from Example 1 is that the chloride salt centrifugation operation is not performed. Instead, the titanium-containing composite single micelle precursor solution is poured into a glass culture dish and the precursor solution is allowed to soak the entire bottom of the culture dish. Then, the excess precursor solution is poured out from the culture dish. The rest of the contents are consistent with Example 1 to obtain a mesoporous TiO2 bulk material.

[0072] Comparative Example 2 Current technology (Dan Feng, Wei Luo, Junyong Zhang, Ming Xu, Renyuan Zhang, Haoyu Wu, Yingying Lv, Abdullah M. Asiri, Sher Bahader Khan, Mohammed M.Rahman, Gengfeng Zheng and Dongyuan Zhao. Multi-layered mesoporous TiO2thinfilms with large pores and highly crystalline frameworks for efficient photoelectrochemical conversion. J. Mater. Chem. A 2013, 1, 1591.) discloses the following preparation method: 0.10g PEO-b-PS was dissolved in 5.0g THF solution and stirred to obtain a uniform solution A (2.0wt%). 0.6g titanium isopropoxide was dissolved in 0.9g acetylacetone solution to obtain a light red solution B. Solutions A and B were mixed, 0.6g concentrated hydrochloric acid (37wt%) was added, and the mixture was stirred for 0.5h to obtain a dark red solution, which was then transferred to a culture dish and the solvent was evaporated at room temperature for about 10min. The culture dish was then transferred to a 40°C oven to further evaporate the solvent for 24h, followed by curing at 100°C for 24h to obtain a light yellow transparent composite film, i.e., the as-made sample was recorded as TiO2-as-made. The as-made sample was calcined at 350°C for 3 h in a tubular furnace under nitrogen atmosphere with a heating rate of 1°C / min. A gray TiO2 / C composite material was obtained after calcination in nitrogen, and the obtained material was recorded as TiO2-N. The composite material was then calcined in air at 500°C for 2 h to obtain a white crystallized mesoporous TiO2 film material, which was recorded as TiO2-A. The difference from Example 1 is that titanium isopropoxide and acetylacetone are used as the titanium source and the hydrolysis inhibitor, and the centrifugation method of chloride salt is not used.

[0073] Comparative Example 3 Prior art (Xiangfen Jiang, Norihiro Suzuki, Bishnu Prasad Bastakoti, Wei-Jung Chen, Yu-Tzu Huang, and Yusuke Yamauchi. Controlled Synthesis ofWell-Ordered Mesoporous Titania Films with Large Mesopores Templated bySpherical PSb-PEO Micelles. Eur. J. Inorg. Chem. 2013, 3286.) discloses the following preparation method: 50mg PS-b-PEO was dissolved in 1.5mL tetrahydrofuran (THF) to prepare a polymer solution at 40°C. After cooling to room temperature, 0.5mL ethanol was added and stirred for 20min. In another flask, 150µL of tetrabutyl titanate was quickly added to 200µL of concentrated hydrochloric acid. A light yellow solid intermediate was observed. The intermediate was easily soluble in high concentration hydrochloric acid to form a dark yellow transparent solution. Then 300µL of deionized water was added, and the solution became colorless. After stirring for 10min, the solution was dripped into the polymer solution and stirred for 30min. The obtained precursor solution was spin-coated on the substrate at a rotation speed of 3000rpm and a rotation time of 30s. After coating, it was aged for 1h at 23°C and 30% relative humidity. After aging, it was calcined at different temperatures in air at a heating rate of 1°C / min for 4h to remove PS-b-PEO and induce crystallization to obtain a mesoporous TiO2 thin film material.

[0074] The difference from Example 1 is that no additional hydrolysis inhibitor was used and no centrifugation method with chloride salts was used.

[0075] Application Example 1 The two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material prepared in Example 1, carbon black, sodium carboxymethyl cellulose and isopropanol were mixed in a mass ratio of 8:1:1:10, and the obtained mixed slurry was coated on the surface of a copper sheet, and then placed in a vacuum oven with a vacuum degree of 120 Pa and dried at 80°C for 12 h to obtain a negative electrode. The loading amount of the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material in the negative electrode was 2.0 mg cm -2 ; Metallic sodium was used as the counter electrode (positive electrode), 1.0 mol / L NaClO4 was dissolved in ethylene carbonate (EC) and propylene carbonate (PC) in a volume ratio of 1:1 as the electrolyte, and glass microfiber was used as a separator to assemble it with the above-mentioned negative electrode in a glove box filled with argon to obtain a button battery (sodium ion battery).

[0076] Performance Testing (1) Figure 1 This is the SEM image of the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material prepared in Example 1.

[0077] from Figure 1 It can be seen that the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material prepared in Example 1 is a large-area two-dimensional ultra-thin porous nanomesh, and the mesopores are highly ordered in a hexagonal form on the entire sheet to form a periodic structure.

[0078] (2) Figure 2 This is the TEM image of the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material prepared in Example 1.

[0079] from Figure 2 It can be seen that the mesopore size of the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material is uniform and is a circular through hole.

[0080] (3) Figure 3 This is the HR-TEM image of the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material prepared in Example 1, and the inset is the SAED image.

[0081] from Figure 3 It can be seen that the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material is in a highly crystalline state, and the interplanar spacing shown corresponds to the (101) crystal plane of TiO2.

[0082] (4) Figure 4 HAADF-STEM and EDS elemental analysis diagram of the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material prepared in Example 1.

[0083] from Figure 4 It can be seen that Ti and O elements are evenly distributed in the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material.

[0084] (5) Figure 5 These are the AFM test images and single-layer thickness information images of the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material prepared in Example 1, where a is the AFM scan image and b is the height information image at the drawn line.

[0085] from Figure 5It can be seen that the thickness of the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material is about 17 nm.

[0086] (6) Figure 6 This is the XRD pattern of the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material prepared in Example 1.

[0087] Depend on Figure 6 It can be seen that the diffraction peak of the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material is completely consistent with the standard card of anatase phase TiO2, proving the successful preparation of the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material.

[0088] (7) Figure 7 The nitrogen adsorption-desorption isotherm and pore size distribution diagram of the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material prepared in Example 1.

[0089] from Figure 7 It can be seen that the nitrogen adsorption-desorption isotherm of the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material shows a characteristic type IV curve, with an obvious capillary condensation step at P / P0=0.5~1.0, indicating that the TiO2 nanomesh contains uniform mesopores.

[0090] from Figure 7 It can be seen that the specific surface area calculated by the Brunauer–Emmett–Teller (BET) method is about 92 m 2 The corresponding pore size distribution curve was deduced from the adsorption branch of the isotherm by using the Barrett−Joyner−Halenda (BJH) method, which clearly showed a pore size centered at 25 nm.

[0091] (8) Figure 8 TEM images of two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh materials with different through-hole center distances, where a and e are from Example 2, b and f are from Example 3, c and g are from Example 1, and d and h are from Example 4. Figure 8 It can be seen that the shortest distances between the edges of adjacent through holes are 5.2nm, 13.0nm, 18.2nm to 26.4nm, respectively, and the center distances between two adjacent through holes can be adjusted between 30.2nm, 38.0nm, 43.2nm and 51.4nm. By adjusting the amount of organic titanium compounds added to control the number of cluster oligomers assembled with the amphiphilic block copolymer to form micelles, the pore wall thickness of the two-dimensional mesoporous array formed by the two-dimensional assembly of the composite micelles can be adjusted, and the shortest distance between the edges of adjacent mesopores can be effectively regulated.

[0092] (9) The sodium ion battery prepared in Example 1 was subjected to electrochemical tests of rate performance and cycle performance on a computer-controlled battery charge and discharge system. The voltage window was 0.01 to 3.0 V. All electrochemical measurements were performed at room temperature (25 °C). Fig. 9 This is a cycle test diagram of a sodium ion battery when the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material prepared in Example 1 is used as the negative electrode. Fig.10 This is a rate test diagram of a sodium ion battery when the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material prepared in Example 1 is used as the negative electrode.

[0093] from Fig. 9 It can be seen that after 500 cycles, the capacity retention rate of the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material is as high as 100.7%.

[0094] from Fig.10 It can be seen that the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material exhibits excellent rate performance. When the current density increases from 0.2 to 5.0, 10 and 30C, the corresponding reversible charge and discharge specific capacity increases from 180mAh·g -1 Reduced to 122 mAh g -1 、107mAh·g -1 and 81mAh·g -1 .

[0095] (10) Figures 11 to 13 They are SEM images of the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh materials prepared in Examples 5 to 7 respectively.

[0096] Depend on Figures 11 to 13 It can be seen that when ethanol appears in the synthetic solvent, a ring-shaped structure material containing one through hole or small fragments containing several through holes appears in the final product. And as the proportion of ethanol increases, the above discrete structure materials increase. This shows that ethanol is conducive to the dispersion of titanium-containing composite single micelles, so that the titanium-containing composite single micelles can retain some unassembled isolated single micelles or small structures formed by the assembly of a small number of single micelles during the two-dimensional assembly process, and finally form ring structures and small fragments respectively.

[0097] (11) Figures 14 and 15 TEM images of the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh materials prepared in Examples 8 and 9, respectively.

[0098] Depend on Figures 14 and 15 It can be seen that when the amount of acetic acid is reduced, a thicker structure with unclear pores appears locally in the sample, which indicates that the lack of acetic acid does not fully inhibit the hydrolysis of the titanium precursor, which is not conducive to the formation of stable charged titanium oxide clusters, and makes the titanium-containing composite single micelles have a certain degree of adhesion before assembly, and are not completely monodispersed. Therefore, a thicker structure with imperfect structure is formed during the assembly process.

[0099] (12) Figures 16 and 17 TEM images of the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh materials prepared in Examples 10 and 11, respectively.

[0100] Depend on Figures 16 and 17 It can be seen that highly ordered mesoporous two-dimensional TiO2 nanonets are obtained when the centrifugal speed is reduced or increased within a certain range, which indicates that the obtained titanium-containing composite single micelles have sufficient positive charges, resulting in strong electrostatic repulsion between micelles and stable structure of titanium-containing composite single micelles. Therefore, when the centrifugal force is small, sufficient electrostatic repulsion can still remove excess micelles to form a single layer, and a large centrifugal force will not destroy the structure of the micelles and cause them to deform or disintegrate.

[0101] (13) Fig.18 This is the TEM image of the mesoporous TiO2 bulk material prepared in Comparative Example 1.

[0102] Depend on Fig.18 It can be seen that in Comparative Example 1, there is no centrifugal force to assist the assembly, so multiple layers of single micelles are assembled on the substrate to form a very thick film.

[0103] (14) Fig.19 This is the SEM image of the mesoporous TiO2 thin film material prepared in Comparative Example 2.

[0104] Depend on Fig.19 It can be seen that in Comparative Example 2, stable charged titanium oxide composite single micelles are not formed first, and single micelles are assembled to form mesoporous materials. Instead, titanium precursors and surfactant molecules are assembled on the substrate in one step to form mesoporous materials. Without charged single micelles and centrifugal force assistance, single-layer assembly to form a single-layer ultra-thin mesoporous material is impossible, and only very thick film materials can be formed.

[0105] (15) Fig. 20 This is the SEM image of the mesoporous TiO2 thin film material prepared in Comparative Example 3.

[0106] Depend on Fig. 20 It can be seen that in Comparative Example 3, stable charged titanium oxide composite single micelles are not formed first, and single micelles are assembled to form mesoporous materials. Instead, titanium precursors and surfactant molecules are assembled on the substrate in one step to form mesoporous materials. Without charged single micelles and centrifugal force assistance, single-layer assembly to form a single-layer ultra-thin mesoporous material is impossible, and only very thick film materials can be formed.

[0107] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention rather than all the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. Application of a two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material as a negative electrode active material in a lithium ion battery and / or a sodium ion battery, characterized in that: The two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material has a two-dimensional sheet structure of periodically arranged single-layer through holes, and the periodic arrangement is hexagonal close-packed; the thickness of the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material is 10-20nm; the center distance between two adjacent through holes is 30-52nm; The method for preparing the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material comprises the following steps: The amphiphilic block copolymer, a good solvent for the amphiphilic block copolymer, an organic titanium compound, an inorganic acid solution and a hydrolysis inhibitor are mixed to carry out a chelating reaction to obtain a titanium-containing composite single micelle precursor solution; The titanium-containing composite single micelle precursor solution is used to encapsulate chloride salt crystals, and the obtained titanium-containing composite micelles encapsulate the chloride salt crystals and age them to obtain a single-layer ordered mesoporous composite sheet encapsulating the chloride salt crystals; The single-layer ordered mesoporous composite sheet wrapped with chloride salt crystals is calcined, and after removing the chloride salt crystals from the calcined product, the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material is obtained; The mass ratio of the amphiphilic block copolymer to the organic titanium compound is 0.01-0.1:0.1-0.8; The hydrolysis inhibitor includes acetic acid and / or acetylacetone, and the ratio of the mass of the organic titanium compound to the volume of the hydrolysis inhibitor is (0.1-0.8) g: (0.5-2.5) mL; The titanium-containing composite single micelle precursor solution is used to encapsulate the chloride salt crystals by mixing the titanium-containing composite single micelle precursor solution and the chloride salt crystals, shaking them well and then centrifuging them; the centrifugal speed is 3000-6000 rpm; and the centrifugal time is 5-10 min; The aging process includes room temperature aging, low temperature aging after a first heating, and high temperature aging after a second heating. The temperature of the low temperature aging is 40-60°C; the temperature of the high temperature aging is 80-100°C; the time of the room temperature aging, low temperature aging and high temperature aging is 12-24 hours respectively. The roasting includes low-temperature calcination and high-temperature calcination in protective gas in sequence, and a third calcination in air; the temperature of the low-temperature calcination is 300-400°C, and the insulation time is 1-3 hours; the temperature of the high-temperature calcination is 500-600°C, and the insulation time is 1-3 hours; the temperature of the third calcination is 500-600°C, and the insulation time is 1-3 hours.

2. The use according to claim 1, characterized in that: The lateral size of the two-dimensional single-layer highly ordered mesoporous TiO2 nanomesh material is 1-10 μm.

3. The use according to claim 1, characterized in that: The amphiphilic block copolymer includes an amphiphilic diblock copolymer or an amphiphilic triblock copolymer; the amphiphilic diblock copolymer includes polyethylene oxide- block -polystyrene block copolymer; the amphiphilic triblock copolymer includes polyethylene oxide-polypropylene oxide-polyethylene oxide block copolymer; the organic titanium compound includes one or more of tetrabutyl titanate, titanium isopropoxide and titanium n-propoxide.

4. A negative electrode, characterized in that The negative electrode active material is a two-dimensional single-layer highly ordered mesoporous TiO2 nano-mesh material used in any one of claims 1 to 3.

5. A lithium ion battery or sodium ion battery, comprising a positive electrode, a negative electrode, an electrolyte and a separator, characterized in that: The negative electrode is the negative electrode according to claim 4.

Citation Information

Patent Citations

  • Novel titanium dioxide cathode material of power lithium ion cell and preparation method thereof

    CN101814598A

  • Hierarchical TiO2 adopting mixed structure and preparation method of hierarchical TiO2

    CN106430303A

  • Aluminum ion-doped mesoporous titanium dioxide lithium battery anode material and preparation method thereof

    CN108155374A

  • Method for preparing two-dimensional ordered mesoporous nanosheet by inorganic salt interface induced assembling

    CN110127661A

  • Two-dimensional mesoporous titanium oxide nanosheet as well as preparation method and application thereof

    CN116854131A

Cited By

  • Ceramic artificial bone material and preparation method thereof

    CN120943623A